METODE PELAKSANAAN PEKERJAAN PELINDUNG TEBING SUNGAI CIMANUK DESA KARANGSAMBUNG - Robiyana, Asep; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
ABSTRAK Cimanuk River basin is in the management of the Great Hall Cimanuk Cisanggarung and is a unity of the river Cimanuk consisting of 5 regencies namely Garut, Sumedang, Majalengka, Indramayu and Cirebon. Along with the influence of natural factors, there is often a landslide in Cimanuk river lips caused by the increase of the discharge of Cimanuk river water which directly impacts on the area of agricultural land in the village of Karang dial. Therefore, a cliff-protective building is required on the Cimanuk River lip to minimize the likelihood of a landslide that is feared to adversely affect the agricultural area of the surrounding inhabitants. The scour or erosion that occurs in cimanuk river raises unrest for the people around the river. Currently, the impact is large enough that the scours already scrape some rice fields and residential areas around. Therefore, necessary immediate handling to overcome the scours that occurs with the protective buildings of the river cliffs. Researchers offer several types of buildings that have been tailored to the needs of each place based on the cross section of the river. The building is a retaining wall of soil, spun pile, slab, gabions, sheet pile.The building of a cliff protector is a major component of important building structures to prevent the movement of the river Lips by the flow of water and other environmental buildings associated with contoured land or land with different elevations. Briefly the cliff-protective building serves to protect the cliffs from landslides caused by increased water discharge.